Assessment of the vulnerability of landslides and their impact on Road ‎No. ‎‎12 using statistical methods and geographic information systems‎ - Thikrayat Mezal Mahimid; Ahmed Flaieh Fayadh (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: The research aims to analyze areas of vulnerability and landslides along Road No. (12) using fuzzy logic and Geographic Information Systems (GIS) techniques. The study also seeks to identify the factors affecting slope stability, classify risk levels, and suggest preventive measures to improve public safety and reduce damage caused by landslides. Methodology: the current study employed the descriptive and analytical approach. This approach was adopted to study the geological and topographical factors affecting road stability, using remote sensing techniques and a digital elevation model (DEM) to analyze the terrain. Geographic Information Systems (GIS) were also applied to create maps identifying risk areas and analyzing the spatial distribution of landslides. Results: After analyzing the data, the results showed that there are changes in: Climatic and hydrological factors: this represents heavy rainfall leads to soil weakness and the separation of rock masses, especially in areas with steep slopes exceeding 35 degrees; Geological and topographic factors which represents fragile rock formations and the presence of cracks and faults contribute to an increased likelihood of landslides; Human Factors which represents cutting and leveling operations during road construction and maintenance affect the slope balance and increasing the risk of landslides; Finally Slope Angle which represents steep slopes cause rock masses to fall due to gravity and posing a danger to road users. Conclusion: it can be concluded that road No. (12) suffers from frequent landslides due to natural and human factors, threatening infrastructure and public safety. The study recommends enhancing slope stability using engineering stabilization techniques, constructing rock barriers, and improving water drainage. It also recommends the use of continuous monitoring and early warning techniques, and conducting periodic geomorphological studies to reduce risks and achieve road sustainability.